High-internal-phase gel emulsion synergistically stabilized by rosin modified hydroxyethyl cellulose and surfactant and preparation method of high-internal-phase gel emulsion
By utilizing the synergistic effect of rosin-modified hydroxyethyl cellulose and surfactants, the stability and rheological properties of high internal phase emulsions were solved, resulting in high internal phase gel emulsions with high stability and controllable rheological properties at low concentrations, suitable for material template applications.
Patent Information
- Application Number
- CN202511846817.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-02-10
AI Technical Summary
Traditional high internal phase emulsion technology suffers from problems such as insufficient stability, uncontrollable rheological properties, and wide particle size distribution. In particular, it is difficult to form an elastic gel state at low concentrations, and existing methods lack systematic rheological characterization.
Rosin-modified hydroxyethyl cellulose with a specific rosin grafting ratio is used as the main emulsifier. Combined with a surfactant with a specific structure, an elastic-dominant rheological gel emulsion is formed at low concentration through synergistic effect. The particle size is precisely controlled in the range of 10-40 μm, and the half-maximum width of the particle size distribution is reduced by more than 40%.
A high internal phase gel emulsion with high stability and controllable rheological properties at low concentrations was achieved. The emulsion showed no oil-water separation after standing for 6 months, did not flow when inverted, had a concentrated particle size distribution, and exhibited rheological properties with a storage modulus higher than the loss modulus and a loss factor of less than 0.4, making it suitable for material template applications.
Smart Images

Figure CN121495142A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer emulsion material technology, specifically relating to a high internal phase gel emulsion stabilized by rosin-modified hydroxyethyl cellulose and surfactants, and its preparation method. Background Technology
[0002] High internal phase emulsions (HIPEs), as special emulsion systems with a dispersed phase volume fraction exceeding 74%, hold significant value in materials science and industrial applications due to their high loading capacity and structural tunability. However, traditional HIPE technologies face numerous challenges. High concentrations of small-molecule emulsifiers are required to stabilize the emulsion system, increasing costs and potentially affecting product performance. Conventional polysaccharide emulsifiers struggle to form stable water-in-oil emulsions, and emulsions prepared by existing methods often exhibit uncontrollable rheological properties and lack elasticity-dominant characteristics, leading to insufficient structural stability when used as templates. Furthermore, the wide particle size distribution of the emulsion severely impacts the uniformity of subsequent materials. Rosin, a natural biomass resource, has a derivative, dehydroabietic acid, with a rigid tricyclic phenanthrene structure that significantly enhances membrane stability. While grafting rosin groups onto the hydroxyethyl cellulose backbone can regulate the hydrophilic-lipophilic balance, current research still has significant limitations, primarily in achieving an elastic gel state at low concentrations and lacking systematic rheological characterization to demonstrate its elasticity-dominant characteristics. Summary of the Invention
[0003] To address the shortcomings of existing high internal phase emulsion technologies, the present invention aims to provide a high internal phase gel emulsion and its preparation method that utilizes rosin-modified hydroxyethyl cellulose and surfactants for synergistic stabilization. This invention selects rosin-modified hydroxyethyl cellulose with a specific rosin grafting ratio as the main emulsifier and a surfactant with a specific structure as the auxiliary emulsifier. Through the synergistic effect of rosin-modified hydroxyethyl cellulose and surfactants, a gel emulsion with elasticity-dominant rheological properties is formed at low concentrations. Its rheological properties are characterized by a storage modulus consistently higher than the loss modulus and a loss factor less than 0.4. The emulsion exhibits no oil-water separation after standing for 6 months and does not flow when inverted at the target concentration. Simultaneously, it achieves precise control of droplet size within the range of 10-40 μm, with a reduction in the half-maximum width of the particle size distribution exceeding 40%, significantly improving the distribution concentration. Its unique rheological properties and stability provide an ideal foundation system for material template applications.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a highly internal phase gel emulsion synergistically stabilized by rosin-modified hydroxyethyl cellulose and surfactants includes the following steps: Rosin-modified hydroxyethyl cellulose is added to water and swells to obtain an aqueous phase; the concentration of rosin-modified hydroxyethyl cellulose in the aqueous phase is 1.5–4.0 wt%; preferably, the swelling is completed by stirring at 20℃~45℃ for 12~24h; the chemical structural formula of the rosin-modified hydroxyethyl cellulose is as follows: In the formula: for and / or The value of n is 600 to 900.
[0005] A surfactant is added to an organic solvent to obtain an oil phase; the organic solvent is immiscible with water, preferably at least one of soybean oil, castor oil, toluene, and n-heptane; the surfactant has an HLB value of less than 5; the surfactant contains a carbon chain structure with 16-18 carbon atoms; preferably, the surfactant is at least one of Span 80, Span 60, and glyceryl monostearate; the surfactant content in the oil phase is 3 vt% to 5 vt%. The aqueous and oil phases are mixed and emulsified to form a water-in-oil high internal phase gel emulsion. Preferably, the volume ratio of the oil phase to the aqueous phase is 10 vt% to 25 vt%. When the oil-water volume ratio is less than 10 vt%, a high internal phase emulsion cannot be obtained. The emulsification method is mechanical stirring or homogenization, and the stirring or homogenization time is set to 2000-8000 rpm / min for 1-10 min.
[0006] The main emulsifier used in this invention, rosin-modified hydroxyethyl cellulose, is dehydroabscisic acid polyoxyethylene ether grafted hydroxyethyl cellulose. The molecular structure contains polyoxyethylene ether segments (with a degree of polymerization of 5), abbreviated as DA(EO)5GE-g-HEC. The introduction of polyoxyethylene ether segments not only enhances the solubility of the emulsifier, but also facilitates its formation of a "falcon-like" structure with the surfactant in terms of spatial structure.
[0007] The present invention also provides a highly internal phase gel emulsion stabilized by rosin-modified hydroxyethyl cellulose and surfactant, which is prepared by the preparation method described above. The high internal phase gel emulsion showed no oil-water separation after standing at 25℃ for 6 months, and did not flow when the bottle was inverted, indicating that the emulsion type is water-in-oil. The rheological properties of the high internal phase gel emulsion meet the requirement that the storage modulus (G′) is always higher than the loss modulus (G″) during full-frequency scanning, and G′ and G″ have no intersection, exhibiting typical gel emulsion phenomena. The average droplet size in the high internal phase gel emulsion is 10-40 μm. Specifically, when the concentration of DA(EO)5GE-g-HEC is 1.5 wt%, the average droplet size is 40 μm; when the concentration of DA(EO)5GE-g-HEC is 4.0 wt%, the average droplet size decreases to 10-20 μm, and the half-maximum width of the particle size distribution decreases by more than 40% with increasing concentration, showing a small droplet aggregation morphology under a microscope.
[0008] The present invention provides a reference for the stabilization mechanism of high internal phase gel emulsions. Figure 1 , Figure 1 A theoretical arrangement model for the synergistic stabilization of surfactants and DA(EO)5-g-HEC at the oil-water interface in high internal phase emulsions is presented. The DA(EO)5GE-g-HEC molecular structure consists of two parts: rosin as a hydrophobic group, and HEC and polyoxyethylene ether segments as hydrophilic groups. The rigid hydrophobic rosin framework acts as an "anchor" distributed in the oil phase, inducing the self-assembly and adsorption of the HEC framework at the oil-water interface, resulting in a tight arrangement of DA(EO)5GE-g-HEC at the interface. Simultaneously, the surfactant, with an HLB value below 5, has relatively large hydrophilic groups that are distributed as hydrophilic segments in the aqueous phase; the hydrophobic groups are long carbon chains with 16-18 carbon atoms, distributed in the oil phase. Due to the presence of polyoxyethylene ether segments (which have a large spatial structure) in the DA(EO)5GE-g-HEC structure, the surfactant is arranged in a special "tadpole" structure within the DA(EO)5GE-g-HEC molecular structure in the emulsion system. This results in the formation of a "falcon-like" structure between DA(EO)5GE-g-HEC and the surfactant at the oil-water interface, creating a super-stable interfacial film. Therefore, a highly stable high-internal-phase gel emulsion system is obtained.
[0009] The high internal phase gel emulsion provided by this invention has the following beneficial effects: This invention improves upon the high internal phase gel emulsion, using a rosin-modified hydroxyethyl cellulose and surfactant complex system to prepare a water-in-oil high internal phase gel emulsion under low concentration conditions, achieving a stability of up to 6 months. For the first time, rheological analysis comprehensively demonstrates the emulsion's elastic dominance; during frequency scanning, the storage modulus consistently exceeds the loss modulus with a ratio greater than 2, the loss factor is less than 0.4, and the linear viscoelastic region extends to the 0.02-2.5% strain range, providing a novel rheologically controllable system for materials science. Breakthroughs have been achieved in particle size control, with a distribution concentration increased by over 40%. The average particle size is 40±3 μm at 1.5 wt% concentration and decreases to 15±2 μm at 4.0 wt% concentration, achieving precise control. Excellent long-term stability is demonstrated; the emulsion shows no phase separation after 6 months of standing and does not flow when inverted at the target concentration, providing reliable structural stability for market applications. This invention achieves the formation of an elastically dominated gel state at low concentrations. Through the combined action of a rigid rosin framework and a surfactant, the stability of the oil-water interfacial film is enhanced, and the elastic behavior of the interfacial film is strengthened. The high internal phase gel emulsion prepared by this invention has the properties to serve as a carrier, encapsulate, and control the release of bioactive substances, improving the utilization rate of active substances. It has significant application value in the field of material templates, and is particularly suitable for the synthesis of porous polymers. The elastically dominated characteristics and high stability exhibited by this emulsion provide an ideal basis for template applications, and its gel structure can effectively maintain the template morphology until polymerization is complete. Attached Figure Description
[0010] Figure 1 A diagram illustrating the stabilization mechanism of the high internal phase gel emulsion provided by this invention; Figure 2 The reaction route for the preparation of DA(EO)5GE-g-HEC in this invention is shown below; Figure 3 For the identification of the type of emulsion prepared in Example 1; Figure 4 Macroscopic images of DA(EO)5GE-g-HEC stable emulsions after standing for 6 months under different concentration conditions; Figure 5 Microstructure (A) and particle size distribution (B) of emulsions stabilized with different concentrations of DA(EO)5GE-g-HEC. Figure 6 Rheological properties of high internal phase emulsion stable under different concentration conditions of DA(EO)5GE-g-HEC. Detailed Implementation
[0011] The present invention will be further described below with reference to embodiments, so that those skilled in the art can better understand and implement the present invention, but the embodiments are not intended to limit the present invention.
[0012] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional methods in the prior art, and therefore will not be described in detail; unless otherwise specified, the materials in the following embodiments can be purchased on the market.
[0013] The preparation method of DA(EO)5GE-g-HEC used in the following examples includes the following steps: Step 1, Preparation of dehydroabioxy-based polyoxyethylene (5) glycidyl ether (DA(EO)5GE): DA(EO)5GE was prepared using the method described in paragraphs 28 to 30 of the patent specification with publication number CN115594777A. Its chemical structural formula is as follows: .
[0014] Step 2, Preparation of DA(EO)5GE-g-HEC: DA(EO)5GE-g-HEC was prepared by reacting DA(EO)5GE with hydroxyethyl cellulose. The chemical reaction equation is as follows: Figure 2 As shown, the specific method is as follows: Weigh 2 g of raw material HEC and 10 g of DA(EO)5GE and dissolve them completely in 80 mL of anhydrous DMSO, then transfer the solution to a 250 mL reaction flask and stir. Raise the temperature of the mixed solution to the set temperature of 60 °C, and slowly add a mixed solution of 0.1 g SnCl4 and 10 mL of anhydrous DMSO as a catalyst. Start timing after the addition is complete, and maintain the temperature for 2 h. After the reaction is complete, add ethyl acetate to precipitate a white solid product. Filter the product, redisperse the solid product in distilled water, dialyze for 24 h, distill under reduced pressure, and freeze-dry to finally obtain DA(EO)5GE-g-HEC.
[0015] Example 1: Preparation and performance characterization of 1.5 wt% DA(EO)5GE-g-HEC stable high internal phase emulsion In this embodiment, Span 80 was selected as the surfactant. A method for preparing a high internal phase gel emulsion synergistically stabilized by rosin-modified hydroxyethyl cellulose and Span 80 includes the following steps: 1.5 g of DA(EO)5GE-g-HEC was accurately weighed and added to 98.5 g of distilled water to prepare the aqueous phase. The aqueous phase was then magnetically stirred in a 40°C water bath for 12 hours to ensure complete swelling. 20 mL of toluene was used as the organic solvent in the oil phase, and 4 mL of Span 80 was added and stirred until homogenized. 80 mL of the aqueous phase and 20 mL of the oil phase were premixed in a beaker, and then homogenized at 6000 rpm for 5 min using a high-speed homogenizer to obtain the high internal phase emulsion.
[0016] The high internal phase emulsion prepared in Example 1 was dispersed in the aqueous phase and the oil phase, respectively, and the resulting macroscopic diagram is shown below. Figure 3As shown, the emulsion type can be determined to be a water-in-oil emulsion with a high internal phase.
[0017] Laser particle size analysis revealed an average particle size of 40 μm and a full width at half maximum (FWHM) of 18 μm. Rheological tests showed a particle size distribution of 0.1 seconds. - ¹Viscosity reaches 1.2 × 10⁻⁶ at low shear rates 4 Strain scanning at millipascals per second determined that the linear viscoelastic region covered a strain range of 0.02-1.8%. Frequency scanning at 0.1 radians per second yielded a storage modulus of 520 Pa and a loss modulus of 210 Pa. The loss factor was calculated to be 0.40, confirming the elastic-dominant characteristics.
[0018] Example 2: Preparation and performance characterization of 4.0 wt% DA(EO)5GE-g-HEC stable high internal phase emulsion A method for preparing a high internal phase gel emulsion synergistically stabilized by rosin-modified hydroxyethyl cellulose and Span 80 includes the following steps: Accurately weigh 4.0 g of rosin-modified hydroxyethyl cellulose and add it to 96 g of distilled water to prepare an aqueous phase, with the same treatment conditions as in Example 1. Prepare the oil phase using a mixture of 10 mL soybean oil and 10 mL toluene, and set aside. Add 5 mL of Span 80 and stir until homogenized. Measure 80 mL of the aqueous phase and 20 mL of the oil phase and premix them in a beaker, then homogenize using a high-speed homogenizer at 6000 rpm for 8 min. The resulting emulsion is a typical water-in-oil emulsion, thus obtaining a high internal phase emulsion.
[0019] Laser particle size analysis showed a significant reduction in average particle size to 15 μm and a narrowing of the full width at half maximum (FWHM) to 8 μm. Rheological properties were significantly improved: 0.1 seconds. - ¹The viscosity increases to 8.5 × 10⁻⁶ at the shear rate. 4 The linear viscoelastic region extends to the strain range of 0.02-2.5% in millipascals per second (mPa·s), the storage modulus reaches 3500 Pa, the loss modulus is 950 Pa, the loss factor is reduced to 0.27, and the elastic properties are further enhanced.
[0020] Example 3: Preparation of a 2wt% DA(EO)5GE-g-HEC-stabilized high internal phase emulsion A method for preparing a high internal phase gel emulsion synergistically stabilized by rosin-modified hydroxyethyl cellulose and Span 80 includes the following steps: Accurately weigh 2.0 g of rosin-modified hydroxyethyl cellulose and add it to 98 g of distilled water to prepare an aqueous phase, with the same treatment conditions as in Example 1. Prepare the oil phase using a mixture of 10 mL soybean oil and 10 mL toluene, and set aside. Add 5 mL of Span 80 and stir until homogenized. Measure 80 mL of the aqueous phase and 20 mL of the oil phase and premix them in a beaker, then homogenize using a high-speed homogenizer at 6000 rpm for 8 min. The resulting emulsion is a typical water-in-oil emulsion, thus obtaining a high internal phase emulsion.
[0021] Laser particle size analysis showed a significant reduction in average particle size to 15 micrometers and a narrowing of the full width at half maximum (FWHM) to 8 micrometers. Rheological properties were significantly improved: 0.1 seconds. - ¹The viscosity increases to 8.5 × 10⁻⁶ at the shear rate. 4 The linear viscoelastic region extends to the strain range of 0.02-2.5% in millipascals per second (mPa·s), the storage modulus reaches 3500 Pa, the loss modulus is 950 Pa, the loss factor is reduced to 0.27, and the elastic properties are further enhanced.
[0022] Comparative Example 1: No rosin-modifying components added The aqueous phase was replaced with pure water, and the oil phase formulation and emulsification process were completely consistent with Example 2. The resulting emulsion was a water-in-oil type, and obvious phase separation occurred after standing for 24 hours. The inverted test showed free-flowing characteristics, and it could not form a stable gel structure.
[0023] Comparative Example 2: No Span 80 component added Span 80 was not added to the oil phase, and all other processes were performed exactly as in Example 2. The resulting emulsion was an oil-in-water emulsion. After 15 days of standing, significant phase separation occurred, and the inverted test showed free-flowing characteristics, without the formation of a stable gel structure.
[0024] Comparative Example 3: 1.0 wt% DA(EO)5GE-g-HEC concentration emulsion The aqueous phase concentration was adjusted to 1.0 wt%, and other conditions were completely consistent with those in Example 1. The resulting emulsion was an oil-in-water emulsion, exhibiting flowability in the inversion test, and rheological testing showed an intersection of storage modulus and loss modulus, indicating no dominant elasticity characteristic.
[0025] Comparative Example 4: If Span 80 is replaced with other substances Span 80 was replaced with hexadecyltrimethylammonium bromide (CTAB), and all other conditions were exactly the same as in Example 1. The HLB value of hexadecyltrimethylammonium bromide was 15.8, resulting in an oil-in-water emulsion, not a water-in-oil emulsion. The inversion test showed flowability, and the rheological test showed that the storage modulus and loss modulus intersected, indicating that it did not exhibit elasticity-dominant characteristics.
[0026] Performance Characterization Figure 4 The image shows macroscopic views of high internal phase emulsions stabilized by DA(EO)5GE-g-HEC under different concentrations after standing for 6 months. As can be seen from the image, the high internal phase emulsion stabilized by DA(EO)5GE-g-HEC and Span 80 has strong stability. No stratification was observed after standing for 6 months, and the emulsion remained "fixed" even after the bottle was inverted, showing non-flow characteristics. This indicates that the high internal phase emulsion has gel emulsion properties.
[0027] Figure 5 These are microstructure diagrams (A) and particle size distribution diagrams (B) of emulsions stable with different concentrations of DA(EO)5GE-g-HEC, as shown. Figure 5 As shown in Figure A, the emulsion particle size gradually decreases as the concentration increases from 1.5 wt% to 4.0 wt%. At a concentration of 4.0 wt%, the DA(EO)5GE-g-HEC emulsion has a smaller particle size and is relatively aggregated. This is because under high concentration conditions, more DA(EO)5GE-g-HEC particles are adsorbed at the oil-water interface, forming a larger interfacial film area, thereby reducing the emulsion particle size and making the emulsion more stable.
[0028] from Figure 5 As shown in Figure B, as the surfactant concentration increases from 1.5 wt% to 4.0 wt%, the overall droplet diameter distribution range gradually narrows, and the diameter of the largest droplets in the emulsion decreases. This indicates that increasing the concentration of DA(EO)5GE-g-HEC reduces the dispersion of droplet size in the emulsion, making the droplet diameter more concentrated, and enhances its stabilizing effect on the emulsion, making it easier for the droplets to maintain a smaller size and a more uniform distribution.
[0029] Figure 6 The rheological properties of stable high internal phase emulsions of DA(EO)5GE-g-HEC under different concentration conditions are shown. Figure 6 As shown in Figure A, the storage modulus and loss modulus of stable high internal phase emulsions of DA(EO)5GE-g-HEC at different concentrations remain basically stable within the strain range of 0.02%~2%. Therefore, a strain value of 0.4% was determined for dynamic full-frequency scanning. Figure 6As shown in Figure B, the overall level of storage modulus (G') increases with increasing emulsion concentration, indicating enhanced elastic properties of the emulsion. Meanwhile, the fluctuation range and trend of loss modulus (G'') are also affected by concentration; high-concentration emulsions are more likely to exhibit stable elastic-dominant characteristics at high frequencies. At low frequencies, the viscosity of the emulsion is more pronounced, and the loss modulus (G'') is relatively high; as the frequency increases, the elastic properties of the emulsion gradually strengthen, and storage modulus (G') gradually becomes dominant.
[0030] Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A method for preparing a highly internal phase gel emulsion synergistically stabilized by rosin-modified hydroxyethyl cellulose and surfactant, characterized in that: Includes the following steps: Rosin-modified hydroxyethyl cellulose was added to water and swollen to obtain an aqueous phase; the concentration of rosin-modified hydroxyethyl cellulose in the aqueous phase was 1.5–4.0 wt%. A surfactant is added to an organic solvent to obtain an oil phase; the organic solvent is immiscible with water; the surfactant has an HLB value of less than 5; and the surfactant contains a carbon chain structure with 16-18 carbon atoms. The aqueous phase and oil phase are mixed and emulsified to form a water-in-oil high internal phase gel emulsion. The chemical structural formula of the rosin-modified hydroxyethyl cellulose is as follows: In the formula: for and / or The value of n is 600 to 900.
2. The preparation method according to claim 1, characterized in that: The surfactant is at least one of Span 80, Span 60, and glyceryl monostearate.
3. The preparation method according to claim 1, characterized in that: The organic solvent is at least one of soybean oil, castor oil, toluene, vinylbenzene, and n-heptane.
4. The preparation method according to claim 1, characterized in that: The surfactant content in the oil phase is 3 vt% ~ 5 vt.
5. The preparation method according to claim 1, characterized in that: The oil phase in the high internal phase gel emulsion has a volume percentage of 10 vt% to 25 vt%.
6. The preparation method according to claim 1, characterized in that: The emulsification method is mechanical stirring or homogenization.
7. A highly internal phase gel emulsion synergistically stabilized by rosin-modified hydroxyethyl cellulose and surfactant, characterized in that: It is prepared by the preparation method as described in any one of claims 1 to 6.
8. The high internal phase gel emulsion according to claim 7, characterized in that: The average droplet size in the high internal phase gel emulsion is 10-40 μm.
Citation Information
Patent Citations
Dehydroabietic oxygen group polyoxyethylene glycidyl ether grafted hydroxyethyl chitosan and preparation method thereof
CN115594777A